Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] such that [tex]\((x+2)\)[/tex] and [tex]\((x-1)\)[/tex] are factors of the quadratic expression [tex]\( x^2 + (a+2)x + a + b \)[/tex], we start by considering what it means for these factors to be true.
Given that [tex]\((x+2)\)[/tex] and [tex]\((x-1)\)[/tex] are factors, we can express the quadratic equation as:
[tex]\[ (x+2)(x-1) \][/tex]
Next, we expand [tex]\((x+2)(x-1)\)[/tex]:
[tex]\[ (x + 2)(x - 1) = x(x - 1) + 2(x - 1) = x^2 - x + 2x - 2 = x^2 + x - 2 \][/tex]
Now, this expanded form should be identical to the original quadratic expression [tex]\( x^2 + (a+2)x + a + b \)[/tex]:
[tex]\[ x^2 + (a+2)x + a + b = x^2 + x - 2 \][/tex]
To find the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex], we compare the coefficients of corresponding terms:
For the [tex]\( x \)[/tex]-coefficients:
[tex]\[ a + 2 = 1 \][/tex]
Solving for [tex]\( a \)[/tex]:
[tex]\[ a + 2 = 1 \implies a = 1 - 2 \implies a = -1 \][/tex]
For the constant terms:
[tex]\[ a + b = -2 \][/tex]
We already found [tex]\( a = -1 \)[/tex], so substitute [tex]\( a \)[/tex] into the equation:
[tex]\[ -1 + b = -2 \implies b = -2 + 1 \implies b = -1 \][/tex]
Thus, the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] are [tex]\( -1 \)[/tex] and [tex]\( -1 \)[/tex] respectively.
Therefore, the correct answer is:
[tex]\[ \boxed{-1 \quad -1} \][/tex]
Given that [tex]\((x+2)\)[/tex] and [tex]\((x-1)\)[/tex] are factors, we can express the quadratic equation as:
[tex]\[ (x+2)(x-1) \][/tex]
Next, we expand [tex]\((x+2)(x-1)\)[/tex]:
[tex]\[ (x + 2)(x - 1) = x(x - 1) + 2(x - 1) = x^2 - x + 2x - 2 = x^2 + x - 2 \][/tex]
Now, this expanded form should be identical to the original quadratic expression [tex]\( x^2 + (a+2)x + a + b \)[/tex]:
[tex]\[ x^2 + (a+2)x + a + b = x^2 + x - 2 \][/tex]
To find the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex], we compare the coefficients of corresponding terms:
For the [tex]\( x \)[/tex]-coefficients:
[tex]\[ a + 2 = 1 \][/tex]
Solving for [tex]\( a \)[/tex]:
[tex]\[ a + 2 = 1 \implies a = 1 - 2 \implies a = -1 \][/tex]
For the constant terms:
[tex]\[ a + b = -2 \][/tex]
We already found [tex]\( a = -1 \)[/tex], so substitute [tex]\( a \)[/tex] into the equation:
[tex]\[ -1 + b = -2 \implies b = -2 + 1 \implies b = -1 \][/tex]
Thus, the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] are [tex]\( -1 \)[/tex] and [tex]\( -1 \)[/tex] respectively.
Therefore, the correct answer is:
[tex]\[ \boxed{-1 \quad -1} \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.